Pengaruh Kualitas Pelayanan Terhadap Kinerja Pegawai Dan Iklim Organisasi Sebagai Variabel Intervening (Studi Pada Bank Syariah Indonesia) Kota Metro - Shelva Olyvia Putri Solikhin; Dharmawan; Ana Septiani (Universitas Muhammadiyah Metro, 2025)
This research aims to determine the influence of service quality on employee performance and organizational climate as an intervening variable at the Indonesian Sharia Bank in Metro City. This research is quantitative, where quantitative research is research that uses types of data that can be measured or calculated directly through measuring research variables using numbers. The data analysis technique used is path analysis, which is a method used in causal models that have been formulated by researchers based on scientific substance, namely the theoretical basis and experience of researchers. The research results show that service quality (ξ1) has a direct effect on performance (η2) at Bank Syariah Indonesia Metro City. Service quality (ξ1) has a direct effect on the Organizational Climate (η1) at Bank Syariah Indonesia Metro City Organizational Climate (η1) has a direct effect on Performance (η2) at Bank Syariah Indonesia Metro City